Retinoblastoma in a Young Nigerian Girl: A Case Report From ECWA Eye Hospital, Kano - Emamoke Atima-Ayeni; Ayodele Jacob Orugun; Ugbede Idakwo; Oyeronke Komolafe; Mayor Orezime Atima; Akinfenwa Taoheed Atanda; Waziri Garba Dahiru; Sani Kamarudeen Owolabi; Eisuke Shimizu; Nakayama Shintaro; Emmanuel Oluwadare Balogun; Emeka John Dingwoke (Case Reports in Ophthalmological Medicine)
Conclusion: This case highlights the aggressive progression of advanced retinoblastoma and the consequences of delayed presentation in resource-limited settings. Although the patient demonstrated an initial positive response, clinically tolerating modified exenteration and two cycles of systemic chemotherapy, she rapidly succumbed to the disease. This underscores the critical need for early diagnosis, prompt referral, and improved access to specialized care to enhance outcomes in similar contexts.